Who was Nikola Tesla? - Gigliotti, Jim; Illustrated by Hinderliter, John (New York Penguin Workshop, 2018)
Introduces readers to Nikola Tesla, one of the most influential scientists of all time.
Include Illustration and Bibliography
Keywords: Serbian Americans -- Electrical engineers -- Inventors